HAK DAN KEWAJIBAN ABDI DALEM DALAM PEMERINTAHAN KRATON YOGYAKARTA - Agus Sudaryanto (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2008)
The result of this research indicates that the rights and obligations of abdi dalem in Kraton Yogyakarta have varieties, it depends on their status and function in the government of Kraton Yogyakarta. Some consideration or motivation to be abdi dalem kraton which are taking part in feeling kraton owned, maintaining of kraton culture, alive to be more meaningful, continuing of tradition from generation to the other, a tool of maintaining to magersari right or obtain the sultan’s blessing.